The nationalization and liberalization of the retail trade industry in the Philippines - Brillo, Bing Baltazar C. (Danyag : Journal of Humanities and Social Sciences, 2010)
The Philippine policy experience in the retail trade sector is distinct. Two radical policy shifts have occurred in the industry and these took a circular path. In 1954, the Third Congress passed Republic Act (R.A.) 1180, the Retail Trade Nationalization Act, and in 2000, the Eleventh Congress enacted R.A. 8762, the Retail Trade Liberalization Act. The former was changed from an open to a protectionist policy while the latter was a change from a protectionist to an open policy. Typically, any move to change an existing policy is always contentious and difficult. Those benefitting from the status quo would naturally take action to preserve their advantage; thus, policy change entails winners and losers. In examining the politics of policy change in the retail trade, this paper utilized four factors -- the context, the stakeholders, and the cost benefits equation, policy rationalization, and presidential intervention and concessions -- to systematically outline and explain the policy shifts that occurred.